أثر السلطة العالمة في الإبداع الفكري والأدبي العصر الصنهاجي أنموذجا - مغشيش, عبد المالك (جامعة الوادي - University of Eloued, 2016)
تعددت صور الحياة الثقافية و الفكرية و الأدبية في هذا العصر وارتبطت بواقعهم الحضاري الذي حدثت فيه طفرة نوعية كبيرة حين عد عصرهم بداية لازدهار ثقافي و علمي و أدبي لم يشهد له المغرب مثيلا من قبل، وهذا يعود أساسا إلى أن أمراء الدولة كانوا أهل علم وثقافة أولوا كبير الاهتمام برجالات الأدب والفكر و جميع علوم عصرهم... وفي ظل سلطان عالم نشأت حركة ثقافية وفكرية وأدبية عاكسة للأوضاع السائدة ،أسهمت في النهوض بأدب وثقافة المنطقة وازدهارها حتى نافست بلاد المشرق والأندلس، ولهذا اعتبر الكثير من الدارسين هذه الفترة مرحلة مهمة في تاريخ الأدب المغربي القديم عرفت بعصر الازدهار الثقافي والأدبي، و الفضل يعود للسلطة الحاكمة العارفة وسياستها الاستشرافية الرشيدة في بناء الفكر العقلي البشري المنتج . Colorful images of cultural life and the intellectual and literary in this day and age and the associated cultural their reality that quantum leap large occurred while counting their time the beginning of a cultural prosperity and scientific and literary Morocco has not seen him ever seen before, and this is mainly because the princes of the state were people of science and culture Ulloa warlords great interest in literature and thought, and all the science of their time... Under Sultan world of cultural, intellectual and literary movement originated reflective of conditions, it contributed to the advancement of literature and culture of the region and prosperity even rivaled the Levant and AlAndalus, but this was considered a lot of studying this period an important stage in the history of the old Moroccan literature known as the era of cultural and literary boom, and the credit goes to power ruling knowledgeable and wise policy in building human mental thought the product.
مقال
Keywords: العصر الصنهاجي - للسلطة الحاكمة